2020
DOI: 10.1109/access.2020.2975877
|View full text |Cite
|
Sign up to set email alerts
|

A Content-Based Method for Sybil Detection in Online Social Networks via Deep Learning

Abstract: Online social networks (OSNs) are generally susceptible to Sybil attack, which causes a series of cybersecurity problems and privacy violations. Malicious attackers can create massive Sybils and further utilize those fake identities to launch various Sybil attacks. Therefore, Sybil detection in OSNs has become an urgent security research problem for both academia and industries. The existing content-based methods to detect Sybils base on the combination of manual-design features and machine learning algorithms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…In addition, new type of features should be investigated to boost up the accuracy for real-world implementation and ensure generalizability. Graph neural network-based methods should be explored more in addition to individual feature-based model, to facilitate the detection of social media bot cluster or coordinated attack or campaigns [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, new type of features should be investigated to boost up the accuracy for real-world implementation and ensure generalizability. Graph neural network-based methods should be explored more in addition to individual feature-based model, to facilitate the detection of social media bot cluster or coordinated attack or campaigns [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a less complicated way, another study [44] showed that bot accounts could be detected with a very high accuracy with a combination of CNN and ANN using a single post on the social media; however, it requires a huge amount of tweets (about 1 million) in each class. Gao et al [45] used a self-normalizing CNN, adopted to extract lower features from the multi-dimensional input data, that Neural Computing and Applications were generated from user profiles and the structure of users' local subgraph and a bidirectional self-normalizing LSTM network (bi-SN-LSTM) to extract higher features from the compressed feature map sequence. Their unique technical contribution lied in proposing bi-SN-LSTM network with SELU as the activation function of its recurrent step, which provided unbounded changes to the state value and using alpha dropout to prevent overfitting while training neural networks.…”
Section: Deep Learning Methods For Social Media Bot Detection: Evalua...mentioning
confidence: 99%
“…Gao et al 135 proposed a content‐based Sybil detection method, where the problem of Sybil detection is divided into two subproblems. The method will do the feature extraction from the input data and perform an end‐to‐end classification and returns the list of Sybil account as output.…”
Section: Ml‐based Solutions For Osn Platformmentioning
confidence: 99%
“…However, like all graph-based techniques, the above method fails if the attacker can craftily achieve a vast network with a bunch of real users. Gao et al (2020) [7] incorporated an ensemble of deep learning algorithms which comprised of CNN to extract low level features and bidirectional LSTM to extricate correlated features. These features were fed into Softmax classifier to classify if the account is sybil or not.…”
Section: Related Workmentioning
confidence: 99%